TI_GERICHTE 17.2013.78 vom 22. August 2013 , Infrazione aggravata alla LStup. Trasporto di 2'371.70 grammi di eroina - TI Tribunale d'appello (2013)
Infrazione aggravata alla LStup. Trasporto di 2'371.70 grammi di eroina